AI and Blockchain Integration: Enhancing Security and Transparency in Financial Transactions - Martinez, Daniel; Magdalena, Lena; Savitri, Agnes Novalita (Pandawan Sejahtera Indonesia, 2024)
The integration of Artificial Intelligence (AI) and Blockchain is revolutionizing the financial sector, targeting crucial challenges like security and transparency. This paper explores the synergistic effects of AI and Blockchain on enhancing the security of financial transactions through advanced real-time fraud detection, anomaly identification, and decentralized transaction verification. Employing a comprehensive review of existing literature and case studies, the research investigates how AI’s capabilities in processing vast data volumes can be leveraged alongside Blockchain’s robust, immutable ledger system to mitigate risks in financial operations effectively. The findings reveal that integrating AI with Blockchain not only significantly improves the security by enabling the real-time detection of anomalies but also upholds the integrity and transparency of transactions across distributed ledgers. The results underscore the potential of AI-Blockchain technology to enhance financial transaction frameworks and highlight its capacity to support the achievement of the United Nations Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 16 (Peace, Justice, and Strong Institutions) by fostering more transparent and secure economic environments. The conclusion of the study suggests further research on the scalability of AI-Blockchain integrations and their broader application across various industries, pointing towards a transformative impact on global financial practices.